Spread of Pseudomonas aeruginosa ST274 Clone in Different Niches: Resistome, Virulome, and Phylogenetic Relationship - Gabriela Chichón; María López; María de Toro; Lidia Ruiz-Roldán; Beatriz Rojo-Bezares; Yolanda Sáenz (MDPI AG, 2023)
Pseudomonas aeruginosa ST274 is an international epidemic high-risk clone, mostly associated with hospital settings and appears to colonize cystic fibrosis (CF) patients worldwide. To understand the relevant mechanisms for its success, the biological and genomic characteristics of 11 ST274-P. aeruginosa strains from clinical and non-clinical origins were analyzed. The extensively drug-resistant (XDR/DTR), the non-susceptible to at least one agent (modR), and the lasR-truncated (by ISPsp7) strains showed a chronic infection phenotype characterized by loss of serotype-specific antigenicity and low motility. Furthermore, the XDR/DTR and modR strains presented low pigment production and biofilm formation, which were very high in the lasR-truncated strain. Their whole genome sequences were compared with other 14 ST274-P. aeruginosa genomes available in the NCBI database, and certain associations have been primarily detected: blaOXA-486 and blaPDC-24 genes, serotype O:3, exoS+/exoU− genotype, group V of type IV pili, and pyoverdine locus class II. Other general molecular markers highlight the absence of vqsM and pldA/tleS genes and the presence of the same mutational pattern in genes involving two-component sensor-regulator systems PmrAB and CreBD, exotoxin A, quorum-sensing RhlI, beta-lactamase expression regulator AmpD, PBP1A, or FusA2 elongation factor G. The proportionated ST274-P. aeruginosa results could serve as the basis for more specific studies focused on better antibiotic stewardship and new therapeutic developments.